Improved rate capability and cycling stability of bicontinuous hierarchical mesoporous LiFePO4/C microbelts for lithium-ion batteries. (9th October 2017) - Zhang, Yue; Huang, Yudai; Tang, Yakun; Zhao, Hongyang; Cai, Yanjun; Wang, Xingchao; Guo, Yong; Jia, Dianzeng; Zong, Jun
Abstract : Bicontinuous hierarchical mesoporous LiFePO4 /C microbelts have been synthesized using a simple dual-solvent electrospinning method for the first time. The sample exhibits a high reversible capacity (153 mA h g −1 at 0.5C), and an excellent high rate cycling performance. Abstract : Bicontinuous hierarchical mesoporous LiFePO4 /C (BHM-LFP/C) microbelts have been synthesized using a simple dual-solvent electrospinning method for the first time. The use of a dual-solvent is beneficial for the electrospinning synthesis, which increases the salt solubility, as well as decreases the surface tension to improve the spinnability. The sample exhibits a high reversible capacity (153 mA h g −1 at 0.5C), and achieves an excellent high rate cycling performance. The enhanced electrochemical performance can be attributed to the unique microbelts providing bicontinuous electron/ion pathways, and the thoroughly mesoporous structure facilitating electrolyte penetration, especially for hierarchical architectures, which have three-dimensional diffusion channels for Li + . This method can be extended to fabricate other electrospun multi-element oxide cathode materials for advanced lithium-ion batteries.